The proline-rich antimicrobial peptide B7-005: low bacterial resistance, safe for human cells and effective in zebrafish embryo bacteraemia model - Adriana Di Stasi; Sara Bozzer; Sabrina Pacor; Luigi de Pascale; Martino Morici; Lara Favero; Mariagiulia Spazzapan; Silvia Pegoraro; Roberta Bulla; Daniel N. Wilson; Paolo Macor; Marco Scocchi; et al. (Open Biology)
Proline-rich antimicrobial peptides (PrAMPs) have gained attention due to their antimicrobial properties and low cytotoxicity. B7-005, a small optimized PrAMP, exhibits a broader spectrum of activity than native PrAMPs, due to an antimicrobial mechanism based on inhibiting prokaryotic protein synthesis and destabilizing bacterial membranes. However, the toxicity and the in vivo efficacy of B7-005 remain poorly understood, so in vitro and in vivo microbiology and toxicology experiments were used to assess its suitability as an anti-infective agent. The incidence of resistance towards B7-005 by E. coli was lower than for other PrAMPs and antibiotics; moreover, it maintained antimicrobial activity in the presence of human serum. B7-005 exerted its antimicrobial effect at a much lower concentration than those causing harmful effects on four different cell types, such as membrane permeabilization or non-lytic depolarization of mitochondria. The latter effect may be related to the inhibition of eukaryotic protein synthesis by B7-005 observed in vitro. In a zebrafish embryo model, B7-005 was well tolerated and reduced mortality from pre-existing E. coli bacteraemia. Overall, B7-005 was safe for human cells and effective against systemic infection in vivo, making it a promising lead for developing new antibiotics.